Solving a problem on an edge crack with cohesive zone by the regularization of a singular integral equation - Selivanov, M.F. (Reports of the National Academy of Sciences of Ukraine, 2019)
An edge mode I crack in a semiinfinite plane is considered. The fracture zone at the front of the crack is modeled with the use of the cohesive zone model, which is based on the non-uniform traction-separation law. The singular integral equation with a generalized Cauchy kernel is solved by the collocation method after the regularization, using the method allowing us to consider the coupling of traction and separation. The constructed algorithm for solving the problem also includes the condition of smooth crack closure. The numeric example is built, by meeting the limiting equilibrium condition for the power traction–separation law with a hardening segment. It is established that the regularization in solving the problem has no effect on the value of critical loading.